Effects of a Supportive and Educational Nursing System for Breastfeeding on Maternal Breastfeeding and Milk Flow in Cesarean section Deliveries - Chokdee, Phanitnad (Journal of Nursing, Siam University, 2023)
This semi-experimental study aimed to investigate the impact of a supportive and educative nursing system for breastfeeding on maternal breastfeeding practices and milk flow following cesarean sections. The study included a total of 44 participants, selected based on predefined criteria. Participants were divided into two groups: one comprised of 22 individuals receiving the supportive and educative nursing system for breastfeeding, and the other consisting of a control group of 22 individuals receiving standard nursing care. The research utilized three main instruments: 1) the supportive and educative nursing system for breastfeeding, 2) a breastfeeding capacity evaluation form, and 3) an evaluation form for milk flow. Statistical analysis involved the use of frequency, percentage, mean, standard deviation, Chi-square Test, and T-test. The findings revealed that: 1) mothers who underwent cesarean sections and received the supportive and educative nursing system for breastfeeding achieved significantly higher LATCH scores compared to those in the control group within the initial 48 hours after the cesarean section and during the pre-discharge phase (p < 0.05), and 2) mothers who underwent cesarean sections and received the supportive and educative nursing system for breastfeeding demonstrated a significantly higher rate of milk flow compared to those in the control group within the same time frames and with statistical significance (p < 0.05).